Brassinosteroids: an alternative to vine cultivation to enhance drought tolerance, in semiarid land at Chihuahua, Mexico - Miriam E. MARTÍNEZ-PÉREZ; Teresita de J. RUÍZ -ANCHONDO; Juan L. JACOBO- CUÉLLAR; Rafael Á. PARRA- QUEZADA; León R. HERNÁNDEZ-OCHOA (Notulae Botanicae Horti Agrobotanici Cluj-Napoca)
Chihuahua is an internationally recognized state for its quality in the production of vines (Vitis vinifera), and wines. However, it is exposed to drought events and has presented economic and social problems due to the low availability of fresh water. The aquifers destined for intensive agriculture, such as Cuauhtémoc present the most pronounced deficit and they have been operating with deficits of −197 mm3 year-1. Chihuahua typically receives an average annual rainfall of 224.5 mm. These semiarid ecosystems, with water scarcity, are not suitable for viticulture unless supplementary irrigation is available. One alternative option is to apply brassinosteroids to enhance the response of antioxidant systems under drought stress. Although growers in Chihuahua use auxins, cytokinins, and gibberellins as enhancers in the vine crop, the application of brassinosteroids (BRs) is not yet used, because there is poorly knowledge about their role and its activity involved in the yield and quality components of the vines and their antioxidant capacity. The brassinosteroids are successfully used to increase production, the size and weight of bunches and berries, to improve the color of grapes, to extend their postharvest life, and to increase the tolerance of plants to abiotic stress, specifically drought. Therefore, this review collects, analyses, and summarizes recently published information and highlights the importance of the properties of brassinosteroids as an antioxidant response in metabolism, fruit production, and quality, their postharvest action in vine cultivation, and recommends their safety use for grape-growing areas in Chihuahua, Mexico, and regions in the world that suffer from drought.